The Relationship between Knowledge and Attitude with Menstrual Hygiene Behavior in Adolescent Girls - Shahibah, Shalwa; Shalahuddin, Iwan; Mamuroh, Lilis (GLOBAL HEALTH SCIENCE GROUP, 2024)
Menstrual hygiene or personal hygiene during menstruation in adolescents is very important. Poor menstrual hygiene practices can potentially cause infections such as vaginitis, leucorrhea, and reproductive tract infections. The research aimed to determine the relationship between knowledge and attitudes towards menstrual hygiene behavior in adolescent girls at the Persatuan Islam Tarogong Islamic Boarding School. This study used a quantitative correlation research design with a cross-sectional approach. The study population consisted of all female students in grades 7-9 who had experienced menstruation, with total sampling technique (N=136). Data collection was conducted on February 8, 2024 by administering questionnaires on knowledge, attitudes, and behaviors to respondents. Data were analyzed using the Chi-square test. The correlation test results showed no relationship between knowledge and menstrual hygiene behavior with a P-value=0.995 (P>0.05), but there was a relationship between attitude and menstrual hygiene behavior with a P-value=0.000 (P<0.05). Therefore, it can be concluded that there is no relationship between knowledge and menstrual hygiene behavior, but there is a relationship between attitude and menstrual hygiene behavior in adolescent girls at the Persatuan Islam Tarogong Islamic Boarding School.